AB0649 Morphofunctional penile alterations with severe sperm abnormalities in antiphospholipid syndrome associated with systemic lupus erythematosus. (23rd January 2014) - Rabelo-Júnior, C.N.; Bonfa, E.; Carvalho, J.F.; Cocuzza, M.; Saito, O.; Abdo, C.H.; Silva, C.A.
Abstract : Background: We identified severe sperm abnormalities associated with intravenous cyclophosphamide (IVCYC) use and reduced penile dimensions with no deleterious effect in erectile function in systemic lupus erythematosus (SLE) patients. 1 In contrast, our group recently observed normal testicular function in primary antiphospholipid syndrome (PAPS) patients, in spite of morphofunctional penile abnormalities. Previous arterial thrombosis seemed to underlie this penile alteration in PAPS. 2 There is, however, no systematic study assessing the overall gonadal function in SLE-APS patients. Objectives: To perform global gonadal and sexual function assessments in SLE-APS patients. Methods: We screened initially 38 male APS patients, 28 patients were excluded: previous vasectomy(n=3), refusal to collect sperm sample(n=9), PAPS(n=12) and APS with others rheumatic diseases (n=4). A cross-sectional study was conducted in 10 SLE-APS patients and 20 healthy controls assessed by demographic data, clinical features, systematic urological examination, sexual function, testicular ultrasound, seminal parameters according to WHO, seminal sperm antibodies and hormone profile. Results: The median of current age was similar in SLE-APS patients and controls (36.9 vs. 32.4years, p=0.310), with a higher frequency of erectile dysfunction in the former group (30% vs. 0%, p=0.029). Further analysis revealed that the median penis circumference was significantly reduced in SLE-APS patients with erectile dysfunction compared to patients without this complication [8.17(8-8.5) vs. 9.14(7-10.5)cm, p=0.0397]. In addition, SLE-APS patients with previous arterial thrombosis had a significantly reduced median penis circumference compared to those without this complication [7.5(7-8) vs. 9.18(8-10.5)cm, p=0.039]. Comparing SLE-APS patients and controls, the former had a significant lower median of sperm concentration (41.1 vs. 120.06×10 6 /mL, p=0.003), percentages of sperm motility (47.25 vs. 65.42%, p=0.047), normal sperm forms evaluated by WHO guidelines (11 vs. 23.95%, p=0.002) and Kruger criteria (2.65 vs. 7.65%, p=0.02). The median of FSH levels was significantly higher in SLE-APS group (9.73 vs. 3.32 IU/liter, p=0.025). Regarding seminal analysis, the median of sperm concentration and total sperm count were significantly lower in SLE-APS patients treated with IVCYC versus untreated with this drug [6.87(0-23.5) vs. 63.9(7.5-145)×10 6 /mL, p=0.04; 16.12(0-55.5) vs. 226.25(8.5-471)×10 6 /mL, p=0.035, respectively]. Conclusions: We identified that IVCYC was the major factor for severe and potentially permanent damage to the tests in SLE-APS patients, and observed for the first time an association of reduced penile size with erectile dysfunction and previous arterial thrombosis in these patients. References: Vecchi A, et al.Penile anthropometry in systemic lupus erythematosus patients.Lupus 2011;20:512-8 Rabelo-Júnior CN, et al.Primary antiphospholipid syndrome:morphofunctional penile abnormalities with normal sperm analysis.Lupus 2012(in press). Disclosure of Interest: None Declared